FAKTOR YANG BERHUBUNGAN DENGAN RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJA - Ramadhani, Safrina (Universitas Prima Indonesia, 2023)
Potential health problems for workers are work accidents and occupational diseases. The International Labor Organization (ILO), 1 worker in the world dies every 1 second due to work accidents and 160 workers experience work-related illnesses. Based on the results of interviews conducted with 10 workers, 6 of them had experienced work accidents such as slipping, being contaminated with chemicals from animal feed and being scratched by sharp objects while the other 4 workers had no work accidents. The purpose of this study was to determine the factors associated with occupational safety and health risks in laying hens at PT. Livestock Friends of West Binjai District, Binjai City in 2022.The study used an analytic survey method with a cross sectional approach. The research population consisted of 50 workers with a sample of 50 people taken using the total sampling technique. Data analysis used univariate and bivariate analysis with the chi-square test statistic.The results showed that variable knowledge (p=0.015), use of PPE (p=0.008) and work environment (p=0.001) with occupational health and safety risks in laying hen farm workers.The conclusion of this study is that there is a relationship between knowledge, use of PPE and work environment with occupational safety and health risks in laying hen farm workers. It is suggested that this research can be used as input for the management, regarding the importance of implementing occupational safety and health to prevent work accidents, such as providing training to workers, providing PPE according to the needs of workers.